Gestión de desechos peligrosos hospitalarios generados en los Centros de Salud de Latacunga para la elaboración de asientos alternativos, UA-CAREN, Universidad Técnica de Cotopaxi, periodo 2014 - 2015 - Aguayo García, Edgar Ricardo (2015)
This research provided medical care in Latacunga, and it also carries the generation hazardous waste that specifically to be directly exposed to the environment, they affect environmental factors such as water, soil and air which results can cause alteration in human health in the city. It was used a process, methods and techniques are conducted an analysis of the treatment provided to the hazardous waste in Latacunga, specifically in the district 05D01 Latacunga-Salud. The first step was to perform a diagnostic of the temporary provision, treatment and final disposal that is provided to the waste generated to know closely the routine procedures and visualize the problems caused by the same. The field research was able to identify the hazardous waste generated for the Health Centers....